Pengaruh Penggunaan Media Pembelajaran Interaktif Berbasis Articulate Storyline 3 untuk Meningkatkan Hasil Belajar Peserta Didik pada Materi Struktur dan Fungsi Jaringan Tumbuhan di SMA Negeri 1 Kabila - Frida Maryati Yusuf; Jusna Ahmad; Lilan Dama; Herinda Mardin; Febriyanti Febriyanti; Irhamna Inaku (Postgraduate, University of Mataram, 2023)
The purpose of this research is to know the impact of the use of interactive learning media Articulate Storyline 3 on the learning results of students on the material of plant network systems in High School 1 Kabila. This type of research uses the form of true experimental design as a pretest-posttest control group design. The instrument used is a question of double choice to measure learning outcomes, implementation sheets and leaflets of students' activities as well as responses to the use of media articulate storyline 3. The study results were analyzed using an independent sample t-test based on the N-Gain acquisition. The results of the study showed that there was an increase in the student’s learning outcomes seen from the N-gain result obtained on average for the experimental class of 0.78 and the control class is 0.50. The performance of the expression class has an average of good categories with the largest number with the highest score of 89%, and the activity of the students in the exhibition class acquires a very active category with the greatest number of nials of 88%. Based on the results of the test of the hypothesis in the experimental class and control class obtained a Sign (2 tailed) value of 0.001 with a signification level (α) 0.05, so that the Sign value (2 tailing) is smaller than the signation level (a) 0.05, thus it can be concluded that there is an influence of the use of Articulate Storyline 3 media on the study results of participants on the structure and function of tissue materials in plants.